2005
DOI: 10.1007/s00268-005-7929-3
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Hernia: Early Complication of Abdominal Surgery

Abstract: It has been suggested that early development of the incisional hernia is caused by perioperative factors, such as surgical technique and wound infection. Late development may implicate other factors, such as connective tissue disorders. Our objective was to establish whether incisional hernia develops early after abdominal surgery (i.e., during the first postoperative month). Patients who underwent a midline laparotomy between 1995 and 2001 and had had a computed tomography (CT) scan of the abdomen during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 27 publications
(42 reference statements)
2
80
1
5
Order By: Relevance
“…In the present study, a RAM distance above 20 mm appeared to be the cut‐off point, although earlier studies2 3 suggested that 12‐mm and 15‐mm separation of the fascial edges or RAM distance represent cut‐off points for risk of incisional hernia formation. These differences may be caused by differences in methodology of radiological examination, although it has been shown15 that a RAM distance of 20 mm at the level of the umbilicus is normal in an unoperated population.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In the present study, a RAM distance above 20 mm appeared to be the cut‐off point, although earlier studies2 3 suggested that 12‐mm and 15‐mm separation of the fascial edges or RAM distance represent cut‐off points for risk of incisional hernia formation. These differences may be caused by differences in methodology of radiological examination, although it has been shown15 that a RAM distance of 20 mm at the level of the umbilicus is normal in an unoperated population.…”
Section: Discussioncontrasting
confidence: 63%
“…Several hypotheses have been proposed to explain the development of these hernias1. Surgical technique seems important, and two clinical trials2 3 have suggested that an increased distance between the rectus abdominis muscles (RAM distance) 1 month after surgery predicts later incisional hernia formation.…”
Section: Introductionmentioning
confidence: 99%
“…Only two patients in the NCT group and three patients in the CT group had a follow up <12 months. The mean number of previous abdominal operations was two (range [1][2][3][4][5]. The mean defect size in the NCT group was 8 cm (range [3][4][5][6][7][8][9][10][11] and in the CT group it was 9 cm (range 4-12) with no statistically significant difference between the groups.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, in patients with gynecological malignancies receiving perioperative systemic chemotherapy, the use of biological mesh has been proposed as a prophylactic measure to prevent PIH [1]. The purpose of this study was to compare the rates of hernia recurrence, seroma formation, and wound infection following PIH repair with a biologic prosthesis in a contaminated field, among patients who received perioperative chemotherapy compared to individuals who did not receive chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Its late appearance is due to a little-known mechanisms, such as changes in connective tissue 5,9 . However, studies with metallic markers at the edges of the sheath of the rectus muscles 20 and with CT by measuring the distance between the inside edges of these three muscles 5 , showed that the process that leads to the formation of HIA starts in the first week after surgery and that its clinical manifestation may take years, contributing to both increased weight, the deterioration of patients' physical status and age. This finding emphasizes the responsibility of the surgeon in its prevention by adequate care in both the abdominal wall closure as the prophylaxis of wound infection.…”
Section: Introductionmentioning
confidence: 99%